O trabalho do atendente de call center: adoecimento por LER/DORT e descartabilidade - Santos, Adna Oiridéia Rabelo dos (2006)
Each year a considerable number of workers are obliged to stop working due to work-related health problems. Those who manage to recover and resume their professional activities often do so under certain health restrictions. The objective of the present study was to look into the work-disease-rehabilitation process of workers afflicted with repetitive strain injury (RSI)/work-related musculoskeletal disorder (WRMD). Semistructured interviews were applied to seven operators at a private call center in Ceará (five of whom presented RSI/WRMD), one supervisor and one trade union representative. The findings show that our subjects share a number of characteristics with call center operators described in other studies on RSI/WRMD, such as the prevalence of female workers (>70%) and outsourced jobs. On the other hand, our subjects differed from most studies with regard to their age range (18-22 years) and schooling (relatively high level). Many of our subjects were taking courses at the university in order to improve their professional qualification while on the job. The poor working conditions, long hours and pressure for productivity placed our subjects at increased risk for acquiring RSI/WRMD. In general, when workers present work-related diseases, companies may deny the existence of a causal relationship. When such relationships are recognized workers are referred to treatment and rehabilitation through public health care (SUS). When rehabilitated workers return to their respective companies they are often given jobs below their actual skill level to prevent recurrence of RSI/WRMD. Once the period expires during which rehabilitated workers are protected against dismissal by law, many such workers are laid off. Thus, workers in this category are caught in a dilemma: if they remain on the job after their rehabilitation, they will have to perform activities they consider meaningless or even humiliating, while being discriminated by peers and supervisors, and if they decide return to the labor market, they will do so as recently rehabilitated and not yet fully trained.